1274. Universal HIV and HCV Screening in San Diego Emergency Departments: Implications for Other Settings With a High Density of Free of Charge HIV Screening Programs. (26th November 2018) - Hoenigl, Martin; Coyne, Chris; Blumenthal, Jill; Vilke, Gary; Little, Susan
Abstract: Background: While HIV and HCV testing targeted to high-risk groups results in substantially higher proportions of HIV diagnoses, universal HIV and HCV screening in emergency department (ED) settings is expected to reach populations who do not perceive themselves to be at risk or are otherwise less likely to participate in HIV and HCV testing. As a consequence the CDC recommends routine HIV screening for persons 13–64 years of age, and routine HCV screening for the birth cohort (born between 1945–1965). The objective of this analysis was to evaluate the yield of universal opt-out HIV and HCV screening in the two EDs at the University of California San Diego (UCSD). Methods: In July 2017, electronic medical record (EMR) based universal opt-out HIV screening (Architect HIV antibody [Ab]/HIV p24 antigen detection) for persons aged 13–64 years (excluding persons known HIV+ or reporteing an HIV test within the last 12 months) was implemented in our EDs. The EMR algorithm also identified HIV+ individuals who had been out of care for >12 months. In March 2018, EMR based universal HCV screening for birth cohort was added in both EDs. Results: Over a period of 9 months 7, 303 HIV tests were conducted, resulting in 24 (0.3%) new HIV diagnoses, of which 21 were successfully linked to care. In five individuals without HIV infection Architect gave a false-positive result (specificity 99.93%). In addition, the EMR algorithm identified 38 out of care HIV+ individuals of which 21 were successfully relinked to care. During the 1-month HCV birth cohort screening 963 HCV Ab tests were conducted, of which 106 (11%) resulted positive. At the time being 78 of those seropositive individuals had HCV RNA testing, of which 36 (53%) resulted positive (3.7% of all participants). Conclusion: In San Diego, a setting with a high density of free-of charge HIV screening programs, 1/300 HIV tests in the ED yielded a new HIV diagnosis and in total 21 newly diagnosed individuals were linked to care. Identification of HIV+ out of care individuals yielded in an equivalent number of individuals relinked to care. The rate of newly diagnosed HCV infections exceeded the rate of newly diagnosed HIV infections by >10-fold outlining the importance of screening for HCV in the ED. Disclosures: All authors: No reported disclosures.